Customer orientation, open innovation and enterprise performance, evidence from Ethiopian SMEs - Aklilu Tukela Bekata; Chalchissa Amentie Kero (Cogent Business & Management, 2024)
The objective of this study was to examine the significance of customer-orientation for open innovation and performance of the SMEs. Explanatory research design and multi-stage sampling were used to acquire both primary and secondary data from the study area. The study used structural equation modeling (SEM) to examine the data and research hypotheses in the suggested structural regression model based on the empirical data of 321 SMEs operating in the study area. The SEM results indicated that small and medium-sized enterprises with higher level of customer orientation are more innovative in their performance. The findings also showed that open innovation partially mediated the relationship between consumer orientation and enterprise performance. Hence, the study found that customer orientation creates better value through open innovation, having an indirect effect on the performance of SMEs. The study's findings suggest that enterprise performance can be realized by implementing business strategies that prioritize customer requirements and satisfaction. SMEs can leverage customer insights to create customer-focused innovation strategies that spread acquired knowledge and new ideas throughout internal decision-making processes, ultimately enhancing open innovation and performance of SMEs.
Keywords: 650; Customer orientation; enterprise performance; open innovation; small & medium enterprise; structural equation modeling; Hawassa city